Spatial culture, processional culture and the materialities of social memory in nineteenth-century Sheffield. Issue 3 (1st September 2016) - Griffiths, Sam
ABSTRACT: This article presents research about a wide range of processions and crowd activities in the English industrial city of Sheffield c .1790–1910. It identifies a theoretical weakness in the historical scholarship where an emphasis on the role of procession and protest in symbolically ordering the built environment too often serves to represent it as intrinsically un-ordered and lacking in definition. The effect, it is argued, has been to present symbolic regimes, particularly those of local elites, as something imposed on rather than in any sense arising from quotidian urban performance, and artificially to isolate research into processional and other mass participation activities from the shared material context of a city's spatial culture . The notion of spatial culture is developed with reference to the work of Bill Hillier, Manuel De Landa, and Henri Lefebvre, among others, to propose an interpretative 'mapping' of the relationship between the evolving structure of Sheffield's built form and the development of its processional culture. The research raises the question of how far civic traditions often regarded as 'inventions' in fact arose from the material conditions of urban life itself, in that sense revealing the historicity of social memory.